Serving the Health Care and Leisure Needs of Ethnic Aged in Canada: Implications and Concerns - Karlis George; Stratas Aida; Locke Marianna; Gravelle François; Arora Genie (Sciendo, 2018)
Health care and leisure services, although different, are similar from the perspective that both focus on enhancing quality of life by improving health and wellbeing. Although both of these services are vitally important, some groups such as aged immigrants face a number of barriers that may limit their access to these services. This paper examines and discusses two related areas of the service sector - health care and leisure - and the growing concern to address the needs of Canada's aging population, specifically, aged immigrants. The paper concludes with the following five suggestions for health care and leisure service providers to alleviate barriers faced by Canada's ethnic aged: 1) Recognize that health care and leisure are closely related, 2) Understand the changing nature of society including trends in immigration, 3) Get to know society's diversity of aged immigrants, 4) Evaluate current services provided, and 5) Establish future goals and directions.